Physicians' responses to time pressure: Experimental evidence on treatment quality and documentation behaviour - Souček, Claudia; Reggiani, Tommaso; Kairies-Schwarz, Nadja (Health policy (Amsterdam, Netherlands), 2025)
BACKGROUND: In hospitals, decisions are often made under time pressure. There is, however, little evidence on how time pressure affects the quality of treatment and the documentation behaviour of physicians. SETTING: We implemented a controlled laboratory experiment with a healthcare framing in which international medical students in the Czech Republic treated patients in the role of hospital physicians. We varied the presence of time pressure and a documentation task. RESULTS: We observed worse treatment quality when individuals were faced with a combination of a documentation task and time pressure. In line with the concept of the speed-accuracy trade-off, we showed that quality changes are likely driven by less accuracy. Finally, we showed that while documentation quality was relatively high overall, time pressure significantly lowered the latter leading to a higher hypothetical profit loss for the hospital. CONCLUSIONS: Our results suggest that policy reforms aimed at increasing staffing and promoting novel technologies that facilitate physicians' treatment decisions and support their documentation work in the hospital sector might be promising means of improving the treatment quality and reducing inefficiencies potentially caused by documentation errors.
Keywords: Humans; Czech Republic; lékaři; Česká republika; Physicians; časové faktory; Time pressure; kvalita zdravotní péče; Quality of Health Care; Time Factors; mužské pohlaví; Documentation; Male; Laboratory experiment; Work motivation; lidé; Physician incentives; dokumentace